Maternal dietary patterns during pregnancy and the risk of infantile eczema during the first year of life: a cohort study in northeast China - Xuening Li; Zhe Xiao; Chenyang Li; Qi Chen; Lihong Jia (BMC, 2023)
Abstract Background There are few studies on the relationship between diet during pregnancy and infantile eczema and the conclusions are inconsistent. The aim of the present study was to explore the impact of dietary patterns during pregnancy on infantile eczema. Methods A total of 495 mother-child pairs from a prospective cohort in Shenyang, China was recruited. Information on maternal dietary intake during pregnancy was assessed with a validated self-administered food frequency questionnaire. The data of infantile eczema was assessed using a structured questionnaire. Factor analysis to derive dietary patterns. The relationship between the dietary pattern and infantile eczema was examined by the logistic regression analysis. Results The cumulative incidence of eczema in 6 months and 12 months in northeast China was 45.7% and 57.8%, respectively. Three dietary patterns were identified. There was a tendency for an expose-response relationship between the maternal high-protein dietary pattern during pregnancy and the risk of infantile eczema within 12 months (P for trend = 0.023): the adjusted odds ratio (95% confidence interval) in the Q1, Q2, Q3, Q4 were 1.00 (reference), 1.63 (0.96-2.76), 1.81 (1.06-3.06), and 1.87 (1.09-3.20), respectively. No association between Western and plant-based patterns during pregnancy and infantile eczema within 12 months was found. Infantile eczema within 6 months was not associated with any of the three dietary patterns. Conclusion The maternal high-protein pattern during pregnancy may be a risk factor for infantile eczema during the first year of life.